Increasing frequencies of site-specific mutagenesis and gene targeting in Arabidopsis by manipulating DNA repair pathways - Qi, Yiping; Zhang, Yong; Zhang, Feng; Baller, Joshua A.; Cleland, Spencer C.; Ryu, Yungil; Starker, Colby G.; Voytas, Daniel F.

(untitled) (Genome Research, 2013)
Improved methods for engineering sequence-specific nucleases, including zinc finger nucleases (ZFNs) and TAL effector nucleases (TALENs), have made it possible to precisely modify plant genomes. However, the success of genome modification is largely dependent on the intrinsic activity of the engineered nucleases. In this study, we sought to enhance ZFN-mediated targeted mutagenesis and gene targeting (GT) in Arabidopsis by manipulating DNA repair pathways. Using a ZFN that creates a double-strand break (DSB) at the endogenous ADH1 locus, we analyzed repair outcomes in the absence of DNA repair proteins such as KU70 and LIG4 (both involved in classic nonhomologous end-joining, NHEJ) and SMC6B (involved in sister-chromatid-based homologous recombination, HR). We achieved a fivefold to 16-fold enhancement in HR-based GT in a ku70 mutant and a threefold to fourfold enhancement in GT in the lig4 mutant. Although the NHEJ mutagenesis frequency was not significantly changed in ku70 or lig4, DNA repair was shifted to microhomology-dependent alternative NHEJ. As a result, mutations in both ku70 and lig4 were predominantly large deletions, which facilitates easy screening for mutations by PCR. Interestingly, NHEJ mutagenesis and GT at the ADH1 locus were enhanced by sixfold to eightfold and threefold to fourfold, respectively, in a smc6b mutant. The increase in NHEJ-mediated mutagenesis by loss of SMC6B was further confirmed using ZFNs that target two other Arabidopsis genes, namely, TT4 and MPK8. Considering that components of DNA repair pathways are highly conserved across species, mutations in DNA repair genes likely provide a universal strategy for harnessing repair pathways to achieve desired targeted genome modifications.